Pemahaman Bisnis Syariah Pada Pedagang Sembako di Pasar Niaga Daya Kota Makassar - Darmawangsa, Andi; Hasibuddin, M (Al-Tafaqquh: Journal of Islamic Law, 2021)
Islam governs all human activity, including muamalah, by defining what is permissible (halal) and what is not permissible (haram) (haram). The business conducted in a sharia business must be founded on sharia. All existing laws and regulations are enforced to prevent businesspeople from being blessed with halal prosperity. This study aims to determine the understanding and implementation of sharia-compliant business on basic food traders in the Daya Niaga Market, Makassar City. The type of research used in this research is Field research, which produces descriptive data in the form of written or verbal data from informants and observed behavior. Interviews, observation, and documentation were employed as data analysis strategies in this study. The data was then analyzed utilizing qualitative descriptive methods. The results of this study provide information that the basic food traders at Pasar Niaga Daya Makassar understand sharia business in practice based on religious knowledge obtained from formal and non-formal education